Accelerating development of new shorter TB treatment regimens in anticipation of a resurgence of multi-drug resistant TB due to the COVID-19 pandemic. (December 2021) - Tiberi, Simon; Vjecha, Michael J.; Zumla, Adam; Galvin, Jessica; Migliori, Giovanni Battista; Zumla, Alimuddin
Highlights: In 2019, of an 500, 000 cases of multi-drug resistant TB (MDR-TB), only 186, 772 were diagnosed and 57% of these were cured. The ongoing COVID-19 pandemic poses many challenges for MDR-TB rollout of diagnostics and implementation of latest WHO guidelines for MDR-TB. In anticipation of increased the numbers of MDR-TB cases there is an urgent need for protecting current investments in TB services. To sustain gains being made in MDR-TB control investing more in development of new TB drugs and treatment regimens is a prudent long-term strategy. Abstract: The WHO 2020 global TB Report estimates that in 2019 there were an estimated 500, 000 cases of multi-drug resistant TB (MDR-TB) of which only 186, 772 MDR-TB cases were diagnosed, and positive treatment outcomes were achieved in 57% of them. These data highlight the need for accelerating and improving MDR-TB screening, diagnostic, treatment and patient follow-up services. The last decade has seen three new TB drugs being licensed; bedaquiline, delamanid and pretomanid, and combinations these new, existing and repurposed drugs are leading to improved cure rates. The all oral six month WHO regimen for MDR-TB is more tolerable, has higher treatment success rates and lower mortality. However, the unprecedented ongoing COVID-19 pandemic is having major direct and indirect negative impacts on health services overall, including national TB programs and TB services. This adds further to longstanding challenges for tackling MDR-TB such as cost, rollout of diagnostics and drugs, and implementation of latest WHO guidelines for MDR-TB. In light of COVID-19 disruption of TB services, it is anticipated the numbers of MDR-TB cases will rise in 2021 and 2022 and will affect treatment outcomes further. Investing more in development of new TB drugs and shorter MDR-TB treatment regimens is required in anticipation of emerging drug resistance to new TB drug regimens. There is an urgent need for protecting current investments in TB services, sustaining gains being made in TB control and accelerating roll out of TB diagnostic and treatment services.